2018
DOI: 10.1002/asna.201813501
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐messenger studies of γ‐ray bursts and their cosmic environment

Abstract: Recent results of the international High Energy Astronomy Research Team (HEART, a Czech, Japanese, American, and Hungarian collaboration) are presented. Our multi‐messenger investigations revealed the properties of γ‐ray bursts (GRB) and their host environments. We analyzed Fermi measurement data with our ADWO method, which appeared as a handy tool for identifying short and intermediate‐long GRBs, such as GRB170817. By studying the GRBs' spatial distribution, we discovered two of the largest known formations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…We calculated the statistically unified intrinsic hydrogen column densities with the better resolution foreground (Toth et al, 2019;Hatsukade et al, 2019;Kovács et al, 2019;Suleiman et al, 2022). We used the 5 arcminutes foreground which were obtained from Planck measurements (Rácz et al, 2017;Pinter, 2018). We made the fit without the redshift information -with the same other settings as the catalog parameters -, so the hydrogen column densities were statistically comparable.…”
Section: Reliability Of Resultsmentioning
confidence: 99%
“…We calculated the statistically unified intrinsic hydrogen column densities with the better resolution foreground (Toth et al, 2019;Hatsukade et al, 2019;Kovács et al, 2019;Suleiman et al, 2022). We used the 5 arcminutes foreground which were obtained from Planck measurements (Rácz et al, 2017;Pinter, 2018). We made the fit without the redshift information -with the same other settings as the catalog parameters -, so the hydrogen column densities were statistically comparable.…”
Section: Reliability Of Resultsmentioning
confidence: 99%
“…In addition to all this, several other anomalies (differences from isotropy and homogeneity) were identified based on the angular and spatial distribution of GRBs (Balázs et al, 1999;Pinter, 2018;Tóth et al, 2019;Horvath et al, 2022) It became clear shortly after the first redshift measurement that the distance of the GRBs shows a relation to their duration: the short GRBs are located closer than the long GRBs. But since GRBs occur over a tremendous time scale, it can be suggested that certain properties of them change based on the distance (Bagoly et al, 2003;Pérez-Ramírez et al, 2010;Kovács et al, 2019;Hatsukade et al, 2019;Toth et al, 2019;Suleiman et al, 2022).…”
Section: Introductionmentioning
confidence: 99%